2016
DOI: 10.1080/23744235.2016.1262059
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of secondary preventive therapy on recurrence of tuberculosis in HIV-infected individuals: a systematic review

Abstract: Human immunodeficiency virus (HIV)-infected individuals successfully treated for tuberculosis (TB) remain at risk of recurrence of the disease, especially in high TB incidence settings. We performed a systematic review, investigating whether secondary preventive therapy (sPT) with anti-TB drugs (preventive therapy in former TB patients with treatment success) is an effective strategy to prevent recurrence of TB in this patient group. We searched the databases PubMed, Cochrane Library, EMBASE, Web of Science an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
(33 reference statements)
0
15
0
1
Order By: Relevance
“…A potential approach to prevent recurrent TB is secondary preventative therapy (sPT), by continuing the use of anti-TB therapy following completion of treatment for TB. sPT aims to reduce the incidence of recurrent TB in TB patients who have completed treatment for their most recent episode of TB [100]. The World Health Organization (WHO) recommends the use of isoniazid preventative therapy (IPT) in patients with HIV infection.…”
Section: Preventative Therapy For Recurrent Tbmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential approach to prevent recurrent TB is secondary preventative therapy (sPT), by continuing the use of anti-TB therapy following completion of treatment for TB. sPT aims to reduce the incidence of recurrent TB in TB patients who have completed treatment for their most recent episode of TB [100]. The World Health Organization (WHO) recommends the use of isoniazid preventative therapy (IPT) in patients with HIV infection.…”
Section: Preventative Therapy For Recurrent Tbmentioning
confidence: 99%
“…Relative reductions varied from 55.0 to 82.1%. However, only one of the four studies reported a significant effect on overall survival [100]. Perriens et al described the use of isoniazid (INH) and rifampicin (RIF) twice weekly for an additional 6 months in comparison to a placebo.…”
Section: Tuberculosis 26mentioning
confidence: 99%
“…In high burden populations a number of trials among HIV infected persons have shown the same pattern of marked reduction in rates of active TB among those receiving TPT, as reviewed extensively elsewhere (Bruins and van Leth, 2017;Akolo et al, 2010). Yet, TPT among PLHIV is virtually the only tool currently implemented in high burden populations, with variable success and not rolled out everywhere.…”
Section: Discussionmentioning
confidence: 86%
“…The WHO recommends treatment of latent TB infection (LTBI) for high risk populations that have higher rates of progression from LTBI to active TB disease [37], especially HIV infected patients who are at 19–21 [38] times higher risk of contracting TB [38,39]. The evidence that TPT is effective in preventing TB and reducing mortality among PLWH is compelling [[40], [41], [42]] with the recent TEMPRANO study demonstrating a 37% reduction in mortality at 6 years among PLWH receiving 6 months of TPT [43].…”
Section: Gaps Along Tb and Hiv Care Cascades Impeding Achievement Of mentioning
confidence: 99%